Analisis Pengajuan Notam Pesawat Udara Tanpa Awak Di Pusat Informasi Aeronautika Wilayah Medan - Doloksaribu, Jonatan Satriadi; Maruli Sinaga, Togi Adnan; Permatasari, Novita Ayu; Muzaki, Mochamad Faisal (Jurnal Bisnis dan Operasi Penerbangan, 2025)
This journal analyzes the registration and verification process of NOTAM (Notice to Airmen) submissions in AIS (Aeronautical Information Services) Medan Regional. Currently, there are challenges in the verification process due to errors in the format and content of NOTAM submissions, resulting in inefficient processes. This condition indicates the need for more attention to the quality and format of the raw data provided by the data sources. It is hoped that with greater awareness of the importance of correct format and standards, the verification process can be more efficient. A specific case of verification problem is presented, where errors in the coordinate sequence in the submission of NOTAM PUTA (Unmanned Aircraft) are identified. The solution to this problem involves assistance from the AIS Medan Regional in correcting the sequence and format of the coordinates, which are then resubmitted to the data source. In resolving the issue, the process of verifying the raw data is repeated and it is found to be correct. The author recommends that the Medan Regional Air Navigation Service Office provide socialization to the data sources regarding the format and standards of NOTAM, to prevent repeated verifications in the future. Thus, it is hoped that a better understanding of the correct format and standards can improve the efficiency of the NOTAM registration and verification process in the AIS Medan Regional.